Preparação de polímeros catiônicos orgânicos a partir do amido de milho e da fécula de batata para utilização no tratamento de água - Sartor, Daniela (2021)
This work consists in transforming corn starch and potato starch into organic cationic polymers by means of the cationization process and to evaluate its performance as a new cationic flocculant for use in water treatment, regarding turbidity and color removal. The cationization reactions were carried out through etherification on the starch, carried out with the reagent 3-chloro-2-hydroxypropyltrimethylammonium chloride (CHPTAC) and treated with 25% ethanol. Using the Jar test equipment, it was possible to simulate the coagulation, flocculation and sedimentation processes. It was concluded that the examined conditions of starch etherification guaranteed the preparation of cationic starches with the predefined degree of substitution (DS = 0.069-0.107). The use of cationic starches (corn and potato) as water flocculants in the removal of remaining color and turbidity from raw water on a laboratory scale demonstrated efficient performance, with the formation of flocs of sufficient size to be removed efficiently by the aggregation mechanism, and can be used as water flocculants.